STUDY THE EFFECTS OF TREATING EXPERIMENTAL VAGINAL CANDIDIASIS WITH THYME , OREGANO OIL AND NYSTATIN ON PITUITARY-GONADAL AXIS IN FEMALE RABBITS - Abdulrazak N. Khudair and Jassim M.A.Alkalby; Bushra F. Hasan (Basrah Journal of Veterinary Research)
Essentiaol oil of thymus vulgaris and origanum vulgare were extracted by hexane and analyzed to the component by GC-MAS Gas chromatography. in vivo study was done on seventy two healthy mature non pregnant female rabbits. Animals were divided into nine groups of eight animals for each one. the first group was injected by 0.1ml physiological saline vaginally and served as a negative control group. All other eight groups were immune suppressed by drenching each animal with (5 mg/kg) dexamethasone once daily for 7 days ,group 2 considered as a dexamethasone control group. Other seven groups were infected vaginally with Candida albicans by (1.5)×〖10〗^8 candida cells/ml once daily for 7 days group 3 considered as vaginal candida (positive) control. The sixth groups then treated once daily for 14 days with ( 0.1) ml of oils according to each group:- group 4 was treated with thyme oil orally, group5 treated with thyme oil vaginally ,group 6 treated with oregano oil orally, group 7 treated with oregano oil vaginally, group 8 treated by oral nystatin, Group 9 treated vaginally with nystatin. Blood was drawn from animals at the end of the experiment all experimental animals were sacrificed and pituitaries; ovaries and uteri were collected and fixed in 10% formalin for histological technique. result explained that candidiasis caused significant increase in progesterone, LH and FSH also decreased in estrogen compared to control. Treatment with thyme or oregano oils by two routs showed decrease in progesterone and an increase in estrogen than candidiasis group. So FSH and LH decreased in groups treated with two oils compared to candidisasis group but not reached to normal level. Nystatin decreased all reproductive hormones. results showed improvement of organs structures in treated with thyme or oregano oils